Botulinum toxin injection attenuates nonodontogenic toothache: A case report. Issue 2 (23rd February 2022) - Chavan, Parimal; Raman, SwarnaLakshmi; Waskitho, Arief; Dalanon, Junhel; Yoshihara, Yasutomo; Okura, Kazuo; Miyamoto, Ryosuke; Matsuka, Yoshizo
Abstract: Nonodontogenic myofascial pain on a 39‐year‐old female patient presented with pain in the lower left quadrant of the jaw. Root canal treatment, replacement of inlay, and behavioral modifications were carried out. Injection of botulinum toxin A at left masseter muscle reduced the toothache. Abstract : Nonodontogenic toothache can be difficult to diagnose and can easily be misdiagnosed as a pain of dental origin. Following a proper diagnostic procedure and selecting the suitable treatment plan is of utmost importance. Botulinum toxin can prove to be an effective solution in such cases if administered properly.